EARLY SOLAR SYSTEM TIMESCALES ACCORDING TO 53MN-53CR SYSTEMATICS - IBITIRA - Lugmair G.W.; Shukolyukov A. (My University, 1998)
We present results of a study of the 53Mn-53Cr systematics in various solar system objects: angrites, eucrites, chondrites, diogenites, pallasites, the Earth and the Moon, and SNC meteorites. The primary goal of this study was to explore the capabilities of the 53Mn-53Cr isotope system as a chronometer and as a tracer for events in the early solar system, to obtain chronological information on different classes of meteorites, and to investigate the indigenous distribution of 53Mn in the late nebula.These studies have shown that all meteorite groups investigated so far have excess 53Cr relative to the terrestrial value. A lunar sample exhibits 53Cr/52Cr ratios which are the same as the terrestrial normal. The angrites, several eucrites, and the pallasites show clear evidence for the existence of life 53Mn during their formation while other meteorites were isotopically equilibrated after essentially all 53Mn had decayed. A well defined whole-rock 53Mn-53Cr isochron for the HED (Howardite-Eucrite-Diogenite) parent body was obtained. The isochron indicates that this planetesimal was essentially totally molten and differentiated ~7 Ma before the angrites crystallized. Using the absolute age of the angrites as a time marker this event has occurred 4565 Ma ago, within present uncertainties at the same time when high temperature meteorite inclusions (CAI) were formed in the nebula. The first basalts were deposited onto its surface within less than 3 Ma. The bulk Mn/Cr ratios of the HED parent body (presumably Vesta), the angrites, and the pallasites are consistent with a chondritic Mn/Cr ratio.The results from the SCN meteorites show that their 53Cr excesses are less than half of those found in the other meteorites. Thus, the characteristic 53Cr/52Cr ratio of Mars (assuming SNCs originate from this planet) are intermediate between that of the earth-moon system and those of the other meteorites. When these 53Cr excesses are plotted as a function of the heliocentric distance of the place of origin of the samples then a linear relationship is indicated. Provided that this variation is due to the decay of 53Mn then a radial heterogeneous distribution of 53Mn must have existed in at least the inner early solar system. It is argued that radial fractionation within the nebula, based on the slightly higher volatility of Mn as compared to that of Cr, is an unlikely cause for this distribution. Thus, it must be an intrinsic feature of the late solar nebula. Stochastic mixing processes at the planetary embryo stage did obviously not eradicate this heterogeneity.Based on the 53Mn-53Cr systematics in HED meteorites and in chondrites rather narrow limits are inferred for the age of the solar system or, more accurately, for the start of the decay of 53Mn within the solar nebula; the range of possible values is 4568-4571 Ma. The lower limit is consistent with the Pb-Pb ages of CAI's.